Touchless monitoring in medical-surgical nursing: clinical applications of radar, camera-based and contact-free vital sign technologies: a narrative review - Sonia Das; K. Gomathi Jaganathan; Divya Upreti; Sufiya Salim Inamdar; Poonam Jadhav; Shubhangi Malavade; P. Vanaja; Tamilselvan; Jaivin Jaisingh J.; N. Prabha; Nilesh Surendra Londhe; Mohammed Umar (International Journal of Research in Medical Sciences, 2026)
Touchless monitoring technologies have emerged as an innovative approach to continuous physiological surveillance in medical-surgical nursing by enabling the assessment of vital signs without direct physical contact. Conventional contact-based monitoring systems, although reliable, are associated with limitations such as patient discomfort, skin injury, sensor displacement, false alarms and increased risk of infection transmission. Recent advances in radar-based sensing, camera-based monitoring, remote photoplethysmography, thermal infrared imaging, radiofrequency sensing, ballistocardiography and artificial intelligence (AI) have facilitated accurate, real-time monitoring of respiratory rate, heart rate, body temperature, movement patterns, sleep behaviour and tissue perfusion. This narrative review summarizes current evidence regarding the principles, clinical applications, advantages, challenges and future directions of touchless monitoring technologies in medical-surgical nursing. The reviewed literature indicates that these technologies can enhance early recognition of physiological deterioration, improve patient comfort, preserve skin integrity, reduce unnecessary physical contact and strengthen patient safety across postoperative care, intensive care, burn management, rehabilitation, infection prevention and remote patient monitoring. AI-driven predictive analytics further improve clinical decision-making by identifying subtle physiological changes before overt deterioration occurs. Despite these advantages, barriers including measurement accuracy, motion artefacts, interoperability, cybersecurity, implementation costs, ethical concerns and workforce preparedness continue to limit widespread clinical adoption. Touchless monitoring should be considered a complementary clinical decision-support tool that augments rather than replaces comprehensive nursing assessment. Continued technological innovation, rigorous clinical validation, standardized implementation strategies and ongoing nursing education are essential for the safe, effective and ethical integration of these technologies into evidence-based medical-surgical nursing practice.